What happens to patients in the long term when we do not repair their cuff tears? Ten-year rotator cuff quality of life index (RC-QOL) outcomes following nonoperative treatment of patients with full-thickness rotator cuff tears - Richard S. Boorman, MD, MSc, FRCSC; Kristie D. More, MSc; Sarah L. Koles, MD, MSc, FRCPC (JSES International)
Background: The purpose of this study was to examine long-term, greater-than-ten-year outcomes of patients with full-thickness rotator cuff tears treated nonoperatively. Methods: Patients with a chronic, full-thickness rotator cuff tear (demonstrated on imaging) who were referred by their physician for shoulder surgery were enrolled in this prospective study between October 2008 and September 2010. Patients then participated in a comprehensive nonoperative treatment program. After the three-month program, patients were defined as “successful” or “failed.” “Successful” patients were essentially asymptomatic and did not require surgery. “Failed” patients were symptomatic and consented to surgical repair. All patients were followed-up at 1 year, two years, and five years using a validated, disease-specific rotator cuff quality of life score (the RC-QOL) and whether or not they eventually underwent surgery during these time intervals. All of the patients who participated at the five-year follow-up were contacted for this study between 10 and 12 years (mean 11.4 years) after treatment. Results: Original results from this study showed that 75% of patients were treated successfully with the nonoperative program, while 25% failed and needed surgery. These numbers were maintained at the two-year follow-up and five-year follow-up (previously reported). At greater than ten years, 88 patients were contacted for follow-up. Only two patients crossed-over from “success” at 5 years to “failed” at 10 years. The nonoperative “success” group had a mean RC-QOL score of 80 (SD = 18) at the previously reported two-year follow-up and 82 (SD = 16) at five-year follow-up. Forty-one patients provided follow-up RC-QOL data at a mean of 11.4 years. The mean RC-QOL scores of the successfully treated nonoperative group were actually higher than those who required surgery during the course of the study (success group mean 86, SD = 12; “failed”/surgery group mean 78, SD = 24), although this was not statistically different (P = .27). Two patients had crossed over from the successful group to undergo surgery between 5 and 11 years (one had an acute traumatic injury and the other reported aggravation with activity). Conclusion: Nonoperative treatment is an effective and lasting option for many patients with a chronic, full-thickness rotator cuff tear. While some may argue that nonoperative treatment delays inevitable surgical repair, this long-term study shows that patients can do very well over time.